ANALYSIS OF MOTORCYCLE TRAFFIC SPEED WHICH CREATES NOISE IN FRONT OF WIYATA MANDALA JUNIOR HIGH SCHOOL DURING THE COVID-19 PANDEMIC - Syaiful, Syaiful; Siregar, Hermanto; Rustiadi, Ernan; Hariyadi, Eri Susanto (Universitas Ibn Khaldun Bogor, 2021)
The development of transportation is increasing rapidly from year to year in accordance with existing technological developments, currently transportation plays an important role in human life, roads are the means of transportation that play the most role in this, along with the increasing volume of passing vehicles as well as road widening of course. Produces a new problem that may still be underestimated, that problem is noise. One of them is a place of education or a school that is right next to the main road, namely Wiyata Mandala Junior High School, Bogor Regency. The speed of private vehicles has a significant effect on noise. From all analysis calculations, the biggest equation is found in the first day of the third point of research (Sound Level Meter 3), with a contribution of 28.95%. The calculation below shows, y = 61.62 + 0.004x1 at a distance of 15.25m SLM. This equation means that if there is no decrease in motorbike speed, the noise level on the SLM3 is 61.62 dBA. The second largest equation was obtained in the first day of research at the second point (Sound Level Meter 2) with a contribution of 27.14% based on the calculation of the equation below, y = 64.23 + 0.007x1 with a distance of 3.44m SLM. The purpose of the above equation is that if there is an increase in motorbike speed, private vehicle speed and public vehicle speed, then the noise on the SLM2 is 64.23 dBA. During the Covid-19 pandemic, motorcycles at moderate speed often passed this school area. So based on the results of observations and calculations, it was found that the decrease in motorcycles was 45% which crossed the Wiyata Mandala Junior High School Bogor.